Shear Behavior of an Unreinforced Geosynthetic Clay Liner. Issue 6 (1997) - Eid, H.T.; Stark, T.D.
Abstract : Dry and hydrated specimens of an unreinforced geomembrane-backed geosynthetic clay liner (GCL) were sheared against a textured geomembrane using a torsional ring shear apparatus to study the shear behavior of geomembrane encapsulated bentonite. Shearing of the dry GCL against a textured geomembrane at high normal stresses resulted in failure occurring within the GCL adhesive that attaches the bentonite to the geomembrane backing and not the GCL bentonite/geomembrane interface. This type of failure occurred when both smooth and textured geomembranes were used as the GCL backing material. Conversely, shearing of the hydrated GCL against a textured geomembrane resulted in failure occurring at the GCL bentonite/textured geomembrane interface. The order of hydration and normal stress application was found to significantly affect the GCL/textured geomembrane interface shear strength. The mobilized shear strength of the GCL/textured geomembrane interface does not equal the drained shear strength of bentonite because of the effect of geomembrane texturing and the lack of drainage during dry and hydrated GCL testing, respectively. Finally, the hydrated GCL/textured geomembrane interface exhibits an increase in peak shear strength of approximately 13% per log cycle of the shear rate. Therefore, the selection of a shear displacement rate is important for unreinforced geomembrane-backed GCL/textured geomembrane interface shear tests.